Alcohol use of female UPV Social Science Division students and some social-psychological family related variables. - Katalbas, Junalie D.
The study describe alcohol use and sought to demostrate its relationship to some family related social-psychological variables among 80 randomly selected female students of UPV Social Sciences Division., Design of the study was descriptive correlational. Alcohol use was measured using the alcohol use questionnaire (Piccinelli et al, 1997), which covered items on the frequency and number of alcohol consumption and ability to control drinking. Questionnaires on family related variables, parental control (Rhoner, 2000), parental modeling and family size were developed by the researchers. Data were analyzed using descriptive statistics and Pearson Product Moment Correlation. Results showed that female UPV Social Sciences division students have no risk of alcohol problem. Also, there was a significant correlation between alcohol use and parental modeling. However, the relationship between alcohol use and variables, parental control and family size, were not demonstrated.